تحليل سيميولوجي للحملات الإعلانية الاجتماعية للتوعية حول لقاحات كوفيد-19 أثناء جائحة كورونا في لبنان: دراسة سيميائية على حملة حلنا نتسجل - جمال الدين، زينة نبيل (د محمد أمين الضناوي, 2024)
نظرا لأهمية التوعية حول اللقاحات فيروس كوفيد- ۱۹، شهدت مرحلة وصول اللقاحات إلى لبنان اهتماما إعلاميا شاسعا، تبين ذلك من خلال الحملات الإعلانية الاجتماعية التي قامت بها الجهات الرسمية في لبنان المتمثلة بوزارة الصحة العامة في لبنان، ووزارة الإعلام، ومنظمة الصحة العالمية، واليونيسف، ووحدة إدارة مخاطر الكوارث، كإحدى أبرز وسائل الاتصال التي وظفت في هذا الإطار. تهدف هذه الدراسة إلى التحليل الكيفي للحملات الإعلانية الاجتماعية للتوعية حول اللقاحات فيروس كوفيد- ۱۹، وذلك بالتطبيق على حملة "حلنا نتسجل". وفي هذا السياق، وظفت أداة التحليل السيميولوجي، بهدف كشف الدلالات التعيينية والتضمينية المختلفة التي يحملها فيديو الحملة، ولكشف الاستمالات والرسائل المصممة لخلق الوعي، وتقليل ومواجهة المخاوف المتعلقة بلقاحات فيروس كوفيد- ۱۹، وبناء الاستعداد المطلوب للتطعيم. The arrival of vaccines in Lebanon garnered significant media attention, owing to the importance of raising awareness about the Covid-19 vaccine. This was seen through social advertising campaigns carried out by the Ministry of Public Health, in cooperation with official agencies, as one of the most prominent means of communication that was employed in this frame. This study seeks to qualitatively analyze the social advertising campaigns in raising awareness about the Covid-19 vaccines, by applying it to the “Time to Register Campaign.” In this context, the semiological analysis tool was utilized, with the aim of revealing the various connotations and denotations carried by the campaign video, and to detect solicitations and messages designed to create awareness, reduce and confront fears related to vaccines against the Covid-19 virus, and build the required readiness for vaccination.
Keywords: الحملات الإعلانية -- التوعية الصحية -- جائحة كورونا "كوفيد-19" -- المجتمع اللبناني